A qualitative exploration of the lived experience of inpatients receiving support from the hospital specialist palliative care team (HSPCT), in one acute hospital setting. Issue 3 (1st September 2016) - Black, Anne; Mayland, Catriona; McGlinchey, Tamsin; Gambles, Maureen; Ellershaw, John
Abstract : Background: The importance of person centred care has been dominant in End of Life Care (EoLC) national guidance since publication of the EoLC Strategy in 2008. However, variations in quality of care remain concerning. National frameworks have been developed to enable care providers to drive changes to improve patient care and experience (NPELCP 2015). It is therefore important to explore what patients and those close to them think about services they encounter; it is widely recommended that engaging with service users should inform ongoing service improvement strategies. Aim: In one acute hospital trust: Explore the lived experience of being a hospital inpatient, and receiving support from the HSPCT; Make recommendations to the acute trust regarding improving patient experience. Method: A phenomenological approach was adopted utilising the following methods: Narrative Interviews – In-depth interviews with recently discharged palliative patients; Case note review – key documentation from recent in-patient episode. Results: 20 interviews completed. Qualitative data analysis is currently being undertaken using Thematic Analysis. Initial emerging themes identify the following: Modes of communication impact on perceptions of care; Levels of understanding affect perceptions of control and loss of self; Burden of symptoms impact on patients holistic wellbeing/quality of life; Institutional culture and prior experiences may exacerbate feelings of concern. Conclusion: Study findings will contribute to a greater understanding of the inpatient experience within the acute hospital setting, as well as provide information directly to the acute trust to promote local change and improvements to care delivery. Reference: National Palliative and End of Life Care Partnership (NPELCP). Ambitions for Palliative and End of Life Care: a national framework for local action; 2015. http://endoflifecareambitions.org.uk/ . Accessed June 17, 2016